Solve for z 3z+1-3(z-1)=4

Math
3z+1-3(z-1)=4
Simplify 3z+1-3(z-1).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3z+1-3z-3⋅-1=4
Multiply -3 by -1.
3z+1-3z+3=4
3z+1-3z+3=4
Simplify by adding terms.
Tap for more steps…
Combine the opposite terms in 3z+1-3z+3.
Tap for more steps…
Subtract 3z from 3z.
0+1+3=4
Add 0 and 1.
1+3=4
1+3=4
Add 1 and 3.
4=4
4=4
4=4
Since 4=4, the equation will always be true for any value of z.
All real numbers
The result can be shown in multiple forms.
All real numbers
Interval Notation:
(-∞,∞)
Solve for z 3z+1-3(z-1)=4

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top